Nanoscale ferroelectric-multiferroic materials for energy harvesting applications - Kimura, Hideo; Cheng, Zhenxiang; Jia, Tingting (Micro & nano technologies., 2019)
Nanoscale Ferroelectric-Multiferroic Materials for Energy Harvesting Applications presents the latest information in the emerging field of multiferroic materials research, exploring applications in energy conversion and harvesting at the nanoscale. The book covers crystal and microstructure, ferroelectric, piezoelectric and multiferroic physical properties, along with their characterization. Special attention is given to the design and tailoring of ferroelectric, magnetic and multiferroic materials and their interaction among ferroics. The fundamentals of energy conversion are incorporated, along with the requirements of materials for this process. Finally, a range of applications is presented, demonstrating the progression from fundamentals to applied science. This essential resource describes the link between the basic physical properties of these materials and their applications in the field of energy harvest. It will be a useful resource for graduate students, early career researchers, academics and industry professionals working in areas related to energy conversion.